EXPORT ANALYSIS – INDONESIAN NATURAL RUBBER IMPORTS TO THE UNITED STATES, TIONGKOK, AND JAPAN - Iwan Aminudin; Dewi Rohma Wati; Delia Ulfah (AGRIBUSINESS JOURNAL, 2020)
The second largest exporter of natural rubber in the world after Thailand is Indonesia. From 2010 to 2015, Thailand's natural rubber exports reached 19,229,423 tons, while Indonesia grew by 7.5% with total exports reaching 15,309,256 tons. In terms of quality, Indonesia's natural rubber is higher than Thailand's. However, in terms of productivity, the opposite happens, Thailand is superior, so more rubber production is produced. The analysis method used is a quantitative model by compiling a simultaneous equation system model estimated by the Two Stages Least Square (2 SLS) method and then processed with the help of Statistical Analysis System 9.1 (SAS). This study used secondary data in the form 1996-2015.The research instruments that are the factors that affect Indonesia's natural rubber imports from the United States, Tiongkok, and Japan are the amount of Indonesia's natural rubber production, the volume of Natural Rubber imports from Tiongkok and Japan in the previous year, Japan's GDP. Then the factors affecting Indonesia's natural rubber exports to the United States, Tiongkok, and Japan are Indonesia's natural rubber production, Indonesia's natural rubber exports to other countries, Indonesia's natural rubber export volume to the United States, Tiongkok, and Japan in the previous year. Then the factors affecting the real price of Indonesian natural rubber, the real price of Indonesian domestic natural rubber, the real price of Indonesia's natural rubber exports the real price of world natural rubber in the previous year, the real price of domestic natural rubber in the previous year, the supply of natural rubber in the domestic market, and the export price of Indonesian natural rubber in the previous year.